BIM feasibility for small and medium-sized contractors and subcontractors. Issue 6 (26th April 2023) - Sadeh, Hooman; Mirarchi, Claudio; Shahbodaghlou, Farzad; Pavan, Alberto
Abstract: BIM adoption for SMEs is an imperative topic. It is assumed that construction contractors and subcontractors play a great part in adopting or neglecting an innovative technology due to different factors. We believe this reluctance attribute would be a common factor between these two groups of construction actors and it would further be an indication of sort of behavior these groups have in common. This study intends to make a major contribution to the body of knowledge by investigating BIM feasibility for SMEs. The research method consists of application of a structured online questionnaire distributed Online, out of which 70 responses from the industry were collected and analyzed. Inferential statistics, and hypothesis testing were applied to check the associations among categorical variables via Wilcoxon Signed Ranks Test and Mann-Whitney U Test. The factors between contractors and subcontractors in terms of organizational, technological, economic, and social attributes were compared. Further, contractors were grouped in terms of BIM and software usage, firm size, and partnership by Cluster Analysis. The results show the rankings for contractors were different from the rankings for subcontractors with respect to technological feasibility and the rankings of contractors were all higher than those of subcontractors when partnership was introduced as a differentiating variable.